UEFA Girls Grassroots Project - Literature review - executive summary - Stride, A.; Brazier, R.; Fitzgerald, H.; Lara-Bercial, S.; Staples, M.; Piggott, S. (2019)
This literature review was commissioned by UEFA to develop an evidence base for the forthcoming Girls Grassroots Project, designed and delivered in association with Disney. It is intended that the research and insight gathered as part of this exercise will inform programme design, content and delivery. It is also the starting point for a UEFA girls and women`s football research and evidence partnership. As well as the literature review, an international scoping exercise of best practice in sport programmes for women and girls was undertaken. In total, 27 examples of good practice were identified with key features of these programmes highlighted. These included: programme goals, target audience, recruitment and delivery strategies, and impact.